Flottenbetrieb von elektrischen und autonomen Serviceagenten im städtischen Personennahverkehr - Schmidt, Arwed (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2017)
The work presents a systematic analysis of a large-scale integration of electric and autonomously controlled vehicles with corresponding infrastructure in cities. A framework is formulated assessing transport-related, electrotechnical and economical parameters of the operation of a highly efficient but comfortable road traffic based on renewable energies. Simulation results show potential to replace local motorized individual transport entirely and to reach the targets of the energy transition.